The RICOSRE-FC potential in improving high school students' critical thinking skills - Hardianto Hardianto; Susriyati Mahanal; Siti Zubaidah (JPBIO (Jurnal Pendidikan Biologi), 2023)
Critical thinking skills are essential 21st-century skills to improve using innovative learning. This study aimed to determine the influence of the RICOSRE-FC model in improving the critical thinking skills of high school students in biology learning. The type of research used is a quasy experiment. The population in this study was all students of class XI MIPA SMAN in Soppeng, South Sulawesi, Indonesia. The classes used for the research sample were 6 classes, 2 classes were taught with the RICOSRE-FC model as an experimental group, 2 classes were taught with the RICOSRE model as a positive control group, and conventional learning as a negative control group. The sample was determined using random sampling techniques. The instrument used is an integrated critical thinking skills test essay test with a scoring rubric of 0-5. Data analysis with the one-way ANCOVA test continued with the LSD test. The results of the one-way ANCOVA test show that a p-level score of 0.00<0.05 means that the learning model affects students' critical thinking skills. RICOSRE-FC has the highest corrected average of 77,349, which shows that the RICOSRE-FC model can potentially to empower students' critical thinking skills.